TEACHING INTERNATIONAL STUDENTS: UNIQUE COMPETENCES FOR TEACHING STAFF - Vyacheslav A. Starodubtsev; Evgeniia O. Frantcuzskaia (Высшее образование в России)
The paper considers the problem of development of innovative competences for teaching staff required in the professional field of training international students as supported by the sustained frameworks of teaching service export in the Russian Federation for the period of 2011-2020; the state policy of the Russian Federation within training national labour for foreign countries in Russian education establishments and a range of publications on the topic. A block of unique competences for teaching staff: competences of tolerance, convergence, polymedia, individualization and international standardization is presented as well as their qualitative characteristics. The authors highlight the necessity of holding a corporate interacademic discussion of unique competence functional contents and ways of their development in the system of enhanced training of teaching staff.